Wnt signalling in mouse mesenchymal stem cells: Impact on proliferation, invasion and MMP expression - Karow, Marisa; Popp, Tanja; Egea, Virginia; Ries, Christian; Jochum, Marianne; Neth, Peter (Journal of Cellular and Molecular Medicine, 2009)
Based on the capacity of mesenchymal stem cells (MSC) to differentiate into multiple cell types in vitro and in vivo, MCS may be a suitable source for cell therapy and regeneration strategies. A prerequisite for effective clinical applications of human MSC (hMSC) is a profound knowledge of signal transduction cascades that mediate processes like proliferation, targeted migration and differentiation. Recently, we identified the canonical Wnt signal transduction pathway as a key player in hMSC proliferation and invasion. To evaluate whether those findings are transferable to the equivalent counterparts in mice, we studied important steps in the wingless/int-1 (Wnt) signal transduction pathway in mouse MSC (mMSC) and mMSC carrying a T cell specific transcription factor (TCF)/lymphoid enhancer binding factor (LEF)-reporter transgene. We found that the induction of the canonical Wnt pathway resulted in the up-regulation of the known Wnt target gene cyclin D1, closely associated with an enhanced proliferation capacity of mMSC. Interestingly, the expression of the Wnt target gene membrane type 1-matrix metalloproteinase (MT1-MMP) was diminished in mMSC upon Wnt3a stimulation, which came along with an impaired invasion. In line with these findings, MMP-2 and MMP-9 expression levels in mMSC were also decreased after Wnt3a treatment. In contrast, inhibition of Wnt signalling by the knockdown of the transcriptional activator β-catenin resulted in an up-regulation of MT1-MMP and mMSC invasion. By comparing these findings with the settings in hMSC, major differences in Wnt-regulated MMP expression were observed in mMSC. Thus, our data advice caution when mouse model systems represent the pre-clinical validation of MSC-mediated therapeutical approaches. © 2009 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
CRIS-Team Scopus Importer:2025-02-10
Keywords: β-catenin; Cell therapy; Membrane type 1-matrix metalloproteinase (MT1-MMP); Migration/invasion; Mouse mesenchymal stem cells (mMSC); RNA interference; TCF/LEF-reporter; Wnt signalling